Dental implant placement with flapless and flapped technique: A systematic review - Rojin Asadollahi; Meysam Mohammadi khah; Niknaz Yahyazadehfar; Farnaz Kouhestani; Zahra Tehrani (Universidad de Concepción., 2018)
Aim: This study was aimed to systematically review and compare implant treatment outcome including success and survival rates, marginal bone loss and post-operative pain between flapped and flapless techniques of implant insertion. Material and Methods: An internet search was performed in PubMed and Cochrane Library in June 2018 using relevant keywords limited to human studies and English language. Clinical studies evaluating the survival rate, marginal bone loss (MBL) and rate of complications between flapped and flapless techniques for implant insertion were included. The review process was performed by two reviewers and the relevant data was extracted from the included studies. Data was compared in a qualitative manner. Results: Electronic search resulted in 1872 studies out of which 32 (21 RCTs) were selected based on the inclusion and exclusion criteria including 1528 patients and 3047 implants. No significant difference was found between success and survival rate of implants using two techniques except for one study that reported higher success rate in flapless group. Twelve studies reported higher MBL in the flapped groups while two studies showed higher MBL in the flapless group. Less pain following flapless technique was reported in 9 studies. One study, however, showed more pain in flapless technique. Conclusion: Implant survival rate using flapped and flapless technique is comparable. Also, MBL using flapless technique is similar or less than flapped technique. Concerning post-operative complications, flapless technique would probably have less post-operative pain.